Բագրատունիների վրացական ճյուղի սկզբնավորումը - Նազարյան, Լիանա («Նաիրի» հրատ.)
Until the second half of the 8th century, Tayk was the fiefdom of the Armenian princely Mamikonean family. The Mamikoneans were succeeded by another Armenian noble house, the Bagratids. A member of the Bagratid family from Tayk founded the Georgian branch of the dynasty. Under their command the Georgian princedoms for the first time united in a single state, and the country entered a new and glorious era that lasted for several centuries. So it is of great importance to find out whence, when and how the Bagratids appeared on the Georgian political arena. There are three groups of sources that shed light on the formation of the Georgian branch of the Bagratids: Armenian, Byzantine and Georgian. Although they do not mention the exact date of its formation, it is known to have occurred between the late 8th and early 9th centuries. More detailed information can be found in Georgian sources. The authors of the Georgian Annals keep silent on the relations between the Georgian Bagratids and their Armenian branch, but other sources corroborate this relationship. До второй половины VIII в. Тайк принадлежал одному из армянских княжеских родов, Мамиконянам. После их ухода с политической арены, регионом завладели Багратиды – другой армянский княжеский род. Именно один из них основал грузинскую ветвь той же династии. Под их началом грузинские княжества впервые объединились в единое государство, и страна вступила в новый и славный период, длившийся несколько столетий. Поэтому крайне важно узнать откуда, как и когда Багратиды появились на грузинской политической сцене. Формирование грузинской ветви Багратидов освещается в трех группах источников: армянских, византийских и грузинских. Хотя они не указывают точную дату ее возникновения, однако известно, что это произошло в период с конца VIII по начало IX века. Более подробные сведения об этом можно найти именно в грузинских источниках. Несмотря на то что, авторы ―Грузинской летописи‖ тщательно обходят молчанием факт родства грузинских Багратидов с их армянской ветвью, источники содержат сведения, подтверждающие эту связь.
Keywords: Պատմություն; Գիտաժողովի նյութեր; Տոհմաբանություն